2016
DOI: 10.1152/ajpgi.00145.2016
|View full text |Cite
|
Sign up to set email alerts
|

A human model of restricted upper esophageal sphincter opening and its pharyngeal and UES deglutitive pressure phenomena

Abstract: Oropharyngeal dysphagia due to upper esophageal sphincter (UES) dysfunction is commonly encountered in the clinical setting. Selective experimental perturbation of various components of the deglutitive apparatus can provide an opportunity to improve our understanding of the swallowing physiology and pathophysiology. The aim is to characterize the pharyngeal and UES deglutitive pressure phenomena in an experimentally induced restriction of UES opening in humans. We studied 14 volunteers without any dysphagic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…[5][6][7]26 Larger volumes elicit stronger lingual propulsive forces, which initiate a swallow adapted to accommodate that bolus size. 8,26 The effect of bolus volume on the occlusive pressure between velopharynx and tongue base previously reported by others 27 were clearly observed in this study ( Fig. 2A).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[5][6][7]26 Larger volumes elicit stronger lingual propulsive forces, which initiate a swallow adapted to accommodate that bolus size. 8,26 The effect of bolus volume on the occlusive pressure between velopharynx and tongue base previously reported by others 27 were clearly observed in this study ( Fig. 2A).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, our potential to measure volume‐related contractile pressure differences in this region may be compromised. Studies investigating the symmetry of deglutitive pharyngeal and UES pressures using state‐of‐the‐art three‐dimensional high‐resolution impedance manometry catheters have recently been published . Although it could be argued that circumferential sensors are optimal for pharyngeal manometry the provision of circumferentially averaged results for each sensor is not necessarily akin to obtaining multiple separate, radially orientated readings .…”
Section: Discussionmentioning
confidence: 99%
“…All these are complimented by the contraction of pharyngeal longitudinal muscles contributing to pharyngeal shortening along with contraction of extrapharyngeal suprahyoid muscles. 13,16 Each of these muscle groups may be uniquely amenable to and demonstrate a unique response to a given intervention as has been shown in the case of velopharyngeal muscle group exhibiting increased pressure with swallowing of larger water volumes, 8 a response not reported for the rest of the pharynx.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that increasing the assist pressure level will further reduce the trans‐sphincteric reflux. Earlier studies have shown that assist pressures as high as 40 mm Hg are well tolerated. Therefore, the effect of assist device pressures exceeding 20 to 30 mm Hg merits further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we determined the effect of experimental enhancement of the UES pressure barrier on trans‐sphincteric retrograde flow of gastric refluxate. To enhance the UES pressure, we used an externally applied handmade device that compressed the UES between the cricoid cartilage and the spine in a controlled fashion delivering a constant pressure of 20 to 30 mm Hg . To monitor the intraesophageal and trans‐UES refluxate flow, we used a multisite impedance monitoring technique.…”
Section: Discussionmentioning
confidence: 99%